The association between perceived HIV-related stigma and presentation for HIV/AIDS care in developing countries: A systematic review protocol - Gesesew, H.; Gebremedhin, Amanuel Tesfay; Demissie, T.; Kerie, M.; Sudhakar, M. (University of Adelaide * Faculty of Health Sciences, 2014)
Review question/objective: The objective of this review is to identify the best available evidence regarding the association between perceived HIV-related stigma and presentation for HIV/AIDS care in developing countries. Inclusion criteria: Types of participants: This review will consider studies that include HIV-positive participants aged 15 years and older in developing countries; defined as those countries listed as "low human development" on the 2013 WHO human development index rankings. Patients receiving prior HIV/AIDS care will be excluded from this review. Types of exposure(s): This review will consider studies that evaluate HIV-related stigma. HIV-related stigma may be measured using any validated tool, either by self-administered questionnaire or interviewing method for people living with HIV, health workers, or the general population. Types of outcomes: This review will consider studies that include the following outcomes: Time at presentation for HIV care, measured by immune status or stage of HIV infection. Early presentation for HIV care is defined as WHO stage I or II and CD4 > =200 cells/µL. Late presentation for HIV care is defined as WHO stage III or IV or CD4 < 200 cells/µL.